MODEL PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE - Didik Gunawan; Lala Lala (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to identify and predict financial difficulties using the Altman Z-Score and Zmijewski X-Score models for property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. This type of research is descriptive research. with a quantitative approach. The data used is secondary data in the form of company financial statements. The results showed that based on the Altman model (Z-Score) in 2018 there were 3 companies in the safe zone, 6 companies in the gray zone, and 13 companies in the distress zone. While in 2019 there were 4 companies in the safe zone, 4 companies in the gray zone, and 14 companies in the distress zone. And in 2020 there are 2 companies in the safe zone, 6 companies in the gray zone, and 14 companies in the distress zone. While the results of the research based on the Zmijewski model (X-Score) show that in 2018 there were 21 companies in the safe zone, and 1 company in the distress zone. While in 2019 all companies were in the safe zone, finally in 2020 there were 20 companies in the safe zone, and 2 companies in the distress zone. Keywords : Altman Z-Score, Zmijewski X-Score.